2010
DOI: 10.1029/2009ja014193
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary magnetic field during the past 9300 years inferred from cosmogenic radionuclides

Abstract: We have reconstructed the interplanetary magnetic field (IMF), its radial component, and the open solar magnetic flux using the solar modulation potential derived from cosmogenic 10Be radionuclide data for a period covering the past 9300 years. Reconstructions using the assumption of both constant and variable solar wind speeds yielded closely similar results. During the Maunder Minimum, the strength of the IMF was approximately 2 nT compared to a mean value of 6.6 nT for the past 40 years, corresponding to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 52 publications
7
105
0
1
Order By: Relevance
“…A Grand Minimum does not seem probable. Steinhilber et al (2009Steinhilber et al ( , 2010 have shown that such type minima occur only during negative phases of the Hallstatt period of solar activity and that statement was confirmed by de Jager and Duhau (2012). The Hallstatt cycle (Clilverd et al 2003(Clilverd et al , 2006Muscheler et al 2004) has a length of 2300 years, and it is, as observations show (cf.…”
Section: The Phase Diagram and The Predictability Of Long-term Solar mentioning
confidence: 55%
See 1 more Smart Citation
“…A Grand Minimum does not seem probable. Steinhilber et al (2009Steinhilber et al ( , 2010 have shown that such type minima occur only during negative phases of the Hallstatt period of solar activity and that statement was confirmed by de Jager and Duhau (2012). The Hallstatt cycle (Clilverd et al 2003(Clilverd et al , 2006Muscheler et al 2004) has a length of 2300 years, and it is, as observations show (cf.…”
Section: The Phase Diagram and The Predictability Of Long-term Solar mentioning
confidence: 55%
“…also Fig. 13): During the negative phases of the Hallstatt periodicity of some 2000 years, Grand Minima cluster together (Steinhilber et al 2010). They do not occur during the positive phase.…”
Section: Pulsations?mentioning
confidence: 99%
“…It makes the ∼50% drop in solar wind B M I N (measured above the floor) between the minima preceding cycles 23 and 24 comparable to the corresponding ∼45% drop in DM (Cliver & Ling, 2010). Finally, a floor at ∼2.8 nT accommodates most of the 10,000 year 10 Be-based reconstruction of B from Steinhilber et al (2010) except for several sharp dropouts where B goes to ∼0 nT (Fig. 3). 3.…”
Section: Precursor Relations and The Floormentioning
confidence: 89%
“…Lockwood et al 1999;Rouillard et al 2007) and cosmogenic radionuclides (e.g. Beer et al 1998;Usoskin et al 2007;Steinhilber et al 2010) clearly show a long-term variation of the solar minima values. Thus, maybe the postulated decrease in temperature is indirectly the result of solar magnetism.…”
Section: Discussionmentioning
confidence: 99%